Cardiac sympathetic index identifies patients with Parkinson's disease and REM behavior disorder. (May 2016) - Salsone, Maria; Vescio, Basilio; Fratto, Alessandra; Sturniolo, Miriam; Arabia, Gennarina; Gambardella, Antonio; Quattrone, Aldo
Abstract: Objective: To compare circadian autonomic fluctuations in patients with Parkinson's Disease (PD) with or without REM sleep behavior disorder (RBD) by using heart rate variability (HRV) analysis. Methods: This is a case-control study including 20 PD patients with RBD (PD-RBD) and 20 PD patients without RBD (PD). In all patients, we measured the components of HRV in the frequency domain during 24-h with daytime and night time recordings. Selected variables considered were low-frequency (LF) influenced by the sympathetic system and high-frequency (HF) influenced by the parasympathetic system. Moreover, we calculated night-to-day ratio for both LF (cardiac sympathetic index) and HF (cardiac parasympathetic index) spectral components. Video-polysomnography was performed in all patients to diagnose RBD. Results: Both nocturnal LF and HF spectral power values were significantly higher in PD-RBD patients than in PD patients (P < 0.001 and P = 0.004 respectively). Moreover, in PD-RBD patients LF and HF values were higher at night than during the day while no difference between night time and daytime values was observed in patients with PD. Cardiac sympathetic index value was significantly higher in PD-RBD patients (median 1.83, range 1.65–3.66) than in PD patients (median 0.93, range 0.44–1.3) without overlap of individual values between groups (accuracy 100%). By contrast, cardiac parasympathetic index had sensitivity of 45% and specificity of 100% for differentiating between PD groups. Conclusions: Cardiac sympathetic index distinguishes PD-RBD patients from those with PD on an individual basis, thus representing a valid help in everyday clinical practice for screening of RBD in PD patients. Highlights: We calculated cardiac sympathetic (LF) and parasympathetic (HF) indexes in PD-RBD vs PD. The indexes were calculated as night-to-day ratio for LF and HF spectral components. Nocturnal LF component was significantly higher in PD-RBD than in PD. Cardiac sympathetic index had an accuracy of 100% for identifying RBD in PD. Cardiac parasympathetic had an accuracy of 72.5% for identifying RBD in PD.